(untitled) (Proceedings of the International Conference on Public Health, 2023)
Cervical Cancer is one of the frequently occurring cancers among Indian women, next only to breast cancer. The prime causative agent, Human Papilloma Virus (HPV), strikes young women in reproductive age group. Although screening test (Pap smear) for early diagnosis is available, HPV vaccine provides prevention which is better than cure. Objectives were to assess the awareness regarding cervical cancer and its preventive measures among the adolescent girls and to ascertain the changes in knowledge and vaccine acceptance as result of educational intervention. Interventional study was done in schools, selected as per convenient sampling technique. Sample size, estimated using 14% prevalence and 10% allowable relative error came at 1092. Total 1105 participants belonging to age group 10-19 years were surveyed. We found that most of the participants attained menarche between 13-15 years (52.7%) while 123 (11.1%) had not attained menarche. Only 279 (25.2%) participants had awareness about cervical cancer and only 5.4% knew about HPV vaccines as its preventive strategy. Assessment of post educational intervention knowledge showed an increase in cervical cancer awareness to 1080 (97.7%) and similar for vaccine acceptability. Still 46 (4.2%) girls are hesitant to take vaccine due to various reasons. Strong statistical association was found between education of mother and acceptability of vaccines. To conclude, adolescents and their parents had poor knowledge about the subject. Strengthening of grass root workers (Accredited Social Health Activists & Anganwadi Workers) of public health regarding the same will help to raise the acceptance. This knowledge can be spread by teachers through interaction & co curricular activities.